If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13x + 4x = -52 + 37x Combine like terms: -13x + 4x = -9x -9x = -52 + 37x Solving -9x = -52 + 37x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-37x' to each side of the equation. -9x + -37x = -52 + 37x + -37x Combine like terms: -9x + -37x = -46x -46x = -52 + 37x + -37x Combine like terms: 37x + -37x = 0 -46x = -52 + 0 -46x = -52 Divide each side by '-46'. x = 1.130434783 Simplifying x = 1.130434783
| 3z+5=-10 | | 3(x*x-2x-1)=4(x*x-3x+2) | | 3(x*x-2x-1)-4(x*x-3x+2)= | | 5x+9=9x-11 | | 46-2x=11-9x | | 8d-v=468 | | 2x+8=-22-4x | | 32x+4=93x-4 | | 8d+v=468 | | X^3+5x^2-5x+20=0 | | 3c*8=1 | | r(x+2)-x=0 | | x+-14=48 | | 10v=30+4v | | x-14=48 | | 9x-10=6x+7 | | 5(2y-3)=20 | | x(4x-9)=0 | | 62=8x-10 | | 79=6x-5 | | 15y-8y=42 | | 5y+15x=-10 | | (7x+2x)+(6x+2x)= | | 5(2p-1)=2(p+3) | | 12+8x=132 | | 5(2p-1)=2(p+3)pis | | 15y+3=8 | | 5(2p-1)=2(p+3)p | | 9n-5(5m+6n)= | | 2x-2=-5y | | 8(y-1)=12 | | h=-4.9t^2+12t+1.5 |